2022
DOI: 10.1021/acsapm.2c00890
|View full text |Cite
|
Sign up to set email alerts
|

Digital Light Processing of Highly Filled Polymer Composites with Interface-Mediated Mechanical Properties

Abstract: Digital light processing (DLP) is a popular method of additive manufacturing of thermosetting polymer composites with high resolution. While DLP of composite systems has been demonstrated, only a few studies comment on the role of interfacial interactions on resulting mechanical properties. In this work, high volume fraction (50 vol %) glass microsphere-reinforced composites were fabricated via DLP. The effects of surface chemistry and interfacial interactions on the mechanical and thermal properties of additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…22 In other previous work, we demonstrated that changes to glass microsphere surface chemistry led to interface-mediated mechanical properties. 23 In this work, we extend the principles from both of those reports and show that increasing resin wettability to the glass reinforcement surfaces through resin modification leads to stronger and stiffer composite materials. It is not always practical or feasible to functionalize a reinforcement's surface, so this work demonstrates that improvements in composite stiffness and strength can be made through improving resin wettability.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…22 In other previous work, we demonstrated that changes to glass microsphere surface chemistry led to interface-mediated mechanical properties. 23 In this work, we extend the principles from both of those reports and show that increasing resin wettability to the glass reinforcement surfaces through resin modification leads to stronger and stiffer composite materials. It is not always practical or feasible to functionalize a reinforcement's surface, so this work demonstrates that improvements in composite stiffness and strength can be made through improving resin wettability.…”
Section: Discussionsupporting
confidence: 60%
“…In other previous work, we found that when only non-covalent bonding is available for the composite, decreasing resin contact angles on silane-functionalized surfaces led to stiffer and stronger composites. 23,35 In comparing all of these studies, we observe that surface functionalization leads to more pronounced changes in wettability and mechanical (adhesive and tensile) properties. One likely reason for this difference is that silane coupling agents are able to achieve complete coating of a surface, while migration of resin additives to the glass surface is less effective.…”
Section: Mechanical Properties and Fractographymentioning
confidence: 89%
See 2 more Smart Citations
“…3D printing, also known as additive manufacturing (AM), has received widespread attention from academia and industry for its potential advantages, such as fabricating customized geometry without the need for molds or machining, reducing production costs and extending applicability to a wide range of materials. Common 3D-printing techniques include fused deposition modeling (FDM), , selective laser sintering or melting (SLS/SLM), stereolithography (SLA)/digital light projection (DLP), , and so forth. In 2013, Tibbits et al from MIT first combined AM with smart materials that can change their shape in response to an applied stimulus such as temperature, electricity, light, radiation, and chemical stimuli (such as a pH change). , The use of smart materials in 3D printing adds the fourth dimension of time to create 3D-printed structures with programmable and adaptable shapes, properties, or functionalities and defined this new technology termed “4D printing”.…”
Section: Introductionmentioning
confidence: 99%